Restoration of the spike architectonics in ancient barley excavated at the twelfth-century settlement of Usvyaty - T. V. Semilet; N. V. Smirnova; N. A. Shvachko; O. N. Kovaleva; E. K. Khlestkina (Труды по прикладной ботанике, генетике и селекции, 2024)
Background. The data are presented on the architectonics of ancient barley spikes from the 12th century, excavated in 2019 at Usvyaty Settlement. Modern molecular genetics approaches were used to study domestication genes (Btr1, Btr2, and Vrs) in ancient and contemporary barleys (germplasm accessions preserved at VIR).Materials and methods. The carbonized kernels found by archaeologists during the excavations at Usvyaty were analyzed. Primers for domestication genes were designed, and PCR was performed on contemporary and ancient barley grains. Ancient kernels were studied in accordance with the rules established for organizing a paleogenetics laboratory, which excluded any contamination with contemporary DNA. Fragments of domestication genes from contemporary and ancient barley grain samples underwent Sanger sequencing. Results. Ancient DNA was isolated and enriched. The analysis of domestication gene sequences made it possible to reconstruct the ancient barley spike’s features. Conclusion. The ancient cereal crop architectonics was restored to ascertain a brittle two-row spike of ancient barley